The Law of Urgency in Choosing Leaders in The Qur'an According to Al-Mawardi - U. Abdurrahman; Moh Najib; Ayi Sofyan (Westscience Press, 2023)
This article explains the mechanism for selecting government and state leaders according to Abu Hassan al-Mawardi's benefit theory. According to al-Mawardi, Islamic teachings require legal norms that are closely related to political and constitutional issues. Based on the interpretation of QS Ali Imran verse 59, al-Mawardi reconstructs the meaning of Ulil Amri as the political representation of the people in the state power system. According to him, Ulil Amri is a group of selected people from various circles, namely soldiers, ulama, scientists, and so on who have an important key in the political decision-making process. The interesting thing about al-Mawardi's thinking is that he emphasizes the political consensus side (ijma fi fiqh al-siyasi) in the process of making political decisions, one of which is used in choosing government and state leaders.